การพัฒนาแบบประเมินทักษะกีฬาเทเบิลเทนนิสตามแนวคิดการประเมินตามสภาพจริงสำหรับนักเรียนมัธยมศึกษาตอนต้น - ชุติมา ศรีเมืองซอง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this research was to develop table tennis skills assessment based on authentic assessment concert for lower secondary school students. The sample for try out, consisted of 30 students and 3 classrooms(105students) for simple random sampling group tennis skills assessment consisted of dip ball forehand and backhand, forehand, backhand, forehand serve, backhand serve, double rally and singles competition. The results of the study was as follows: 1.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.820, 0.714 for the dip ball forehand/backhand 2.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.881, 889 for the forehand 3.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.887, 0.879 for the backhand 4.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.875, 0.794 for the forehand serve 5.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.890, 0.894 for the backhand serve 6.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.717, 0.852 for the double rally 7.The index of congruence(IOC) was 0.800 Validity and Objectivity was 0.701, 0.855 singles competition